Odpowiedzi

2009-09-27T09:23:13+02:00
-1,8 * 2/3 - 0,8 * (-3/4)2 -18/10 * 2/3 – 8/10 * 9/16 -6/5- 9/20
----------------------------- =---------------------------------=----------------- =
-0,9 * 5/9 + (-1/2) -9/10 * 5/9 – ½ -1/2 -1/2

-24/20-9/20 -33/20
=--------------= -----------=
-1 -1
=33/20=1 i 13/20
  • Użytkownik Zadane
2009-09-27T09:46:07+02:00
-1,8 * 2/3 - 0,8 * (-3/4)2
----------------------------- =
-0,9 * 5/9 + (-1/2)

(-18/10*2/3)-(8/10*9/16)
---------------------------------- =
(-9/10*5/9)-1/2

(-9/5*2/3)-(4/5*9/16)
---------------------------- =
-1/2-1/2

(-6/5)-(9/20)
------------------ =
-1

(-24/20)-(9/20)
-------------------- = (-33/20):(-1)= 1 i 13/20
-1